2015
DOI: 10.1038/ejcn.2015.212
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ strategies for eating after gastric bypass surgery: a qualitative study

Abstract: BACKGROUND/OBJECTIVES: There is considerable variation in the amount of weight patients lose after gastric bypass surgery, and this may be related to the way they adjust to the operation in their daily eating practices. Little is known about how this varies. On the basis of a qualitative research design, this study therefore explores how patients deal with gastric bypass surgery in their daily lives. SUBJECTS/METHODS: The study is based on interviews with 24 men and women in Denmark diagnosed with morbid obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…It is argued that, paradoxically, the removal of choice may improve and help re-establish self-control as fewer choices are experienced as a release [11] . Further, the eating strategies patients adopt after weight loss vary [17] suggesting that successful weight maintenance is individual and complex. On this basis, we suggest that a shift in focus from cognitive restraint and control and calorie reduction to patients' context-centered strategies and actual practices may elicit new insights into successful weight loss maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that, paradoxically, the removal of choice may improve and help re-establish self-control as fewer choices are experienced as a release [11] . Further, the eating strategies patients adopt after weight loss vary [17] suggesting that successful weight maintenance is individual and complex. On this basis, we suggest that a shift in focus from cognitive restraint and control and calorie reduction to patients' context-centered strategies and actual practices may elicit new insights into successful weight loss maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Gaining awareness of foods that are low in glycaemic index might also explain the reasons why participants would choose certain types of food that help in prolonging the rise of their BGLs. Hillersdal et al [24] had similar outcomes with their participants' eating habits after BS.…”
Section: Knowledgementioning
confidence: 68%
“…All participants in this current study believed that they were 'cured' from T2DM, which gave them a sense of relief from the burden of managing their BGLs. Non-adherence to a diet plan and lack of exercise are factors that challenge people with uncontrolled T2DM [24]. This study found that BS was used as a method to manage obesity and therefore assist with T2DM management when Kuwaiti patients no longer responded to the medications prescribed or they sought an easier and faster option to manage their T2DM.…”
Section: Knowledgementioning
confidence: 94%
“…Hillersdal's role was to investigate how interdisciplinarity was enacted in practice, and how 'the problem of obesity' co-configured in specific collaborations. She had been involved in the development of the project design, and worked with many of the involved researchers in an earlier project on obesity surgery (Hillersdal et al, 2015(Hillersdal et al, , 2016. Jespersen was part of the steering committee of GO and involved in two of the work packages as a PI of the work package focusing on interdisciplinary work practices and co-PI in a work package centered around a clinical trial investigating the health effects on physical activity (Larsen et al, 2017).…”
Section: Our Positions In the Governing Obesity [2] And Lifestat Projmentioning
confidence: 99%